Honor as Cultural Mindset: Activated Honor Mindset Affects Subsequent Judgment and Attention in Mindset-Congruent Ways - Novin, Sheida; Oyserman, Daphna (Frontiers in Psychology, 2016)
Honor values articulate gender roles, the importance of reputation in maintaining one’s place in society, and maintaining respect for the groups one belongs to. In that sense honor provides a template for organizing social interactions and hence may be functional even among people and societies that do not report valuing and endorsing honor. We test the prediction that honor influences judgment and attention when activated in two experiments (N=538). Using a culture-as-situated cognition perspective, we predicted that activating one aspect of honor would activate other aspects, even among individuals who do not much endorse honor values. We tested these predictions among European Americans, a group that is not typically associated with honor values. In each study, participants were randomly assigned to experimental or control groups, which differed in one way: the experimental group read statements about honor values as a first step and the control group did not. Participants then judged stick-figure pairs (judging which is male; Study 1, n = 130) or made lexical decisions (judging whether a letter-string formed a correctly spelled word; Study 2, n = 408). In Study 1, experimental group participants were more likely to choose the visually agentic figure as male. In Study 2, experimental group participants were more accurate at noticing that the letter-string formed a word if the word was an honor-relevant word (e.g., noble), but they did not differ from the control group if the word was irrelevant to honor (e.g., happy). Participants in both studies were just above the neutral point in their endorsement of honor values. Individual differences in honor values endorsement did not moderate the effects of activating an honor mindset. Though honor is often described as if it is located in space, we did not find clear effects of where our letter strings were located on the computer screen. Our findings suggest a new way to consider how honor functions, even in societies in which honor is not a highly endorsed value.